A Comparative Analysis of Product Cost Determination Using the Full Costing and Variable Costing Methods to Set Selling Prices - Anna Octaviani; Mulyati Mulyati; Dian Urna Fasihat (Yayasan Pendidikan Bukhari Dwi Muslim, 2026)
Purpose: This study analyzes the significant differences in calculating the Cost of Goods Manufactured (COGM) using Full Costing versus Variable Costing for determining selling prices at Mebel Samawa. Research Method: A quantitative, descriptive, comparative approach using a case study strategy was employed. Secondary data from production cost documents were analyzed through COGM calculations, statistical difference tests via Microsoft Excel, and cost-plus pricing simulations. Results and Discussion: Results show a significant COGM difference between the two methods across all products, with a consistent variance of IDR 13,131 per unit due to fixed overhead cost treatments. Annually, this variance reaches IDR 35,440,569. The company's actual selling prices exceed both calculations, indicating an adequate profit margin. Implications: Custom-made MSMEs should adopt Full Costing as the primary pricing basis to recover all operational costs, utilizing Variable Costing solely for short-term tactical decisions. Originality: This research provides a comprehensive statistical test of differences between two COGM methods, directly evaluating their implications for real pricing strategies within a micro-scale furniture enterprise.